FOLKLOR SUNDA UNTUK PENINGKATAN KARAKTER PEDULI SOSIAL ANAK USIA 5-6 TA HUN - Yayu Mega Purnamasari; Ayu Rissa Atika (IKIP Siliwangi, 2022)
Social care is needed in a social environment to create a harmonious, respectful and empathetic community environment. The inculcation of social care characters needs to be introduced and taught from an early age so that children can understand differences with others and have concern. Instilling social care characters can be done in various ways, although the delivery needs to be done carefully, considering that the middle child is in the concrete preoperational phase so that the delivery needs to be simplified, one of which is through Sundanese folklore . This study aims to determine the effectiveness of Sundanese folklore to improve the social care character of children aged 5-6 years. The method used is quasi-experimentalwith pretest - posttest control group design. The population in this study were children aged 5-6 years in Tasikmalaya, using a sample of 30 children. samples were taken using purposive sampling technique. The data collection technique was through interviews and observations of social care characters, while data analysis used the homogeneity test, normality test, t-test with a significance level of 0.05. The results of this study indicate that Sundanese folklore iseffective in improving the social care character of children aged 5-6 years.Peduli sosial diperlukan dalam lingkungan sosial untuk menciptakan lingkungan masyarakat yang harmonis, saling menghargai dan memiliki empati. Penanaman karakter peduli sosial perlu dikenalkan dan diajarkan sejak dini agar anak dapat memahami perbedaan dengan orang lain serta memiliki kepedulian. Karakter peduli sosial dapat ditanamkan melalui berbagai cara, salah satunya melalui folklore sunda. Penelitian ini bertujan untuk mengetahui tingkat efektivitas folklore sunda untuk meningkatkan karakter peduli sosial anak usia 5-6 tahun. Metode yang digunakan yakni quasi eksperimen dengan pretest-postest control group design. Populasi dalam penelitian ini adalah anak berusia 5-6 tahun di Tasikmalaya, dengan menggunakan sampel sebanyak 30 anak. sampel diambil menggunakan teknik purposive sampling. Pengumpulan data melalui observasi karakter peduli sosial, adapun analisis data menggunakan uji homogenitasm uji normalitas, t-test dengan tingkat signifikansi 0,05. Penelitian ini menunjukan bahwa folklore sunda efektif untuk meningkatkan karakter peduli sosial anak usia 5-6 tahun.